Hubungan antara Social Relationship Satisfaction dengan Digital Social Interaction Preference pada Dewasa Awal - Najwa Salvabillah Putri Rahdiansyah; Erik Saut H. Hutahaean; Ferdy Muzzamil (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine the relationship between social relationship satisfaction and digital social interaction preference in early adulthood. The development of digital technology encourages individuals to use digital media as a means of social interaction, but high preference for digital social interaction does not necessarily lead to high social relationship satisfaction. This study employed a quantitative method with a correlational design. A total of 172 early adult respondents (aged 18–25 years) were obtained through purposive sampling. The instruments used were the Preference for Online Social Interaction (POSI) scale and the Relationship Assessment Scale (RAS). Data analysis used Kendall's Tau-b correlation test because the data was not normally distributed. The results showed a correlation coefficient of 0.158 with a significance value of 0.003 (p 0.05), indicating a positive and significant but very weak relationship between the two variables. The majority of respondents had a high level of digital social interaction preference (73.3%), while the majority had low social relationship satisfaction (57.6%). These findings indicate that digital media can support social interaction, but is not the primary determinant of social relationship satisfaction in early adulthood.